THE EMIRATE OF BUKHARA AND INDIA BETWEEN TEA TRADE IN THE SECOND HALF OF THE 19TH AND EARLY 20 TH CENTURIES - Ibrohimov Nozimjon Ikhtiyorovich (American Journals Publishing, 2025)
In the second half of the 19th century and the beginning of the 20th century, the number of Indians living in Central Asia was significant. Indians settled compactly in the caravanserais of Central Asia. They created a unique way of life in each region, and if there were no caravanserais nearby, they settled in one area and created “Indian rows” and “Indian neighborhoods”. Indian society in Central Asia consisted of representatives of the emerging national capital, who mainly dealt with trade and monetary matters. Those who came from India, in addition to trade and usury, also engaged in entrepreneurship. Among the Indians were cooks, bakers, and confectioners.
Keywords: Caravanserai, protectorate, indigo, khalmuri, hisson, pari, patta, nauzugur, usury, kanaus, kaliko, pud, pound, mile, export, import.